Alterity, Friendship, and Solidarity Buddhists, Christians, and James Fredericks - Hábito, Rubén L.F. (Buddhist Christian studies, 2018)
This essay discusses three key themes that mark James Fredericks's lasting contribution to Buddhist-Christian dialogue. In his (hitherto unpublished) doctoral dissertation, Fredericks examines the work of Tanabe Hajime, a Buddhist philosopher of the Kyoto School on the one hand, and on the other, that of Karl Rahner, a Catholic theologian who was a major influence in the Second Vatican Council, and finds a resonant theme in their works as he considers the notion of "alterity," a middle way between the pitfalls of monism and dualism with regard to the relationship of Ultimate Reality and worldly phenomena, of God and Creation. A second theme is his ongoing emphasis on the practice of interreligious friendship between Buddhists and Christians, which can lead to the discovery of untold intellectual and spiritual treasures and to mutual enrichment for both sides. Friendship can then become a firm basis for a stance of solidarity, overcoming religious differences, and grounding cooperative work toward justice, peace, and ecological healing.